A política externa estadunidense no atual quadro político sul-americano - Silva, Luiz Fernando da [UNESP] (My University, 2011)
The central thesis that we aim to survey in this paper is that the present South-American political scene has required of the American imperialism a strategical redesign, in the sense of the neutralization, weakening and, if it is possible, destruction of regional political experiences/tendencies not aligned to its foreign politics. Under the mask of the defense of democracy and beneath the argument that Latin American "market oriented politics" are at stake, due to questions that goes back from the "delin-quency" —in Mexico—, the global terrorism, the organized international crime up to the worldwide drug traffic, the global strategy of American imperialism then sets up the definition of a new doctrine of preventive war that justifies the utilization of hard power against any country, in the name of its own defense. At the heart of the question what —actually— is in the agenda is the defense (and reproduction) of the benefits of its multinationals corporations and financial capital, by means of the international sub-traction of profitable assets, such as financial, energetic, communicational and natural resources, in addition to the domination of local markets, beyond facilitating capital flee amongst others.

La tesis central que intentamos investigar en este artículo es que el presente escenario político sudamericano ha demandado del imperialismo estadounidense una redefinición estratégica, en el sentido de neutralizar, debilitar y, si es posible, destruir experiencias/tendencias políticas regionales no alineadas a su política externa. Desde la máscara de la defensa de la democracia y del argumento de que las "políticas orientadas hacia el mercado" latinoamericano están en riesgo, por problemas que van desde la "delincuencia" —en México—, el terrorismo global, el crimen organizado internacional hasta el narcotráfico mundial, la estrategia global del imperialismo americano entonces perialismo americano entoncespasa a establecer una nueva doctrina de guerra preventiva que justifica la utilización del poder bélico contra cualquier país, en nombre de su propia defensa. En el centro de la cuestión lo que —de hecho— está en el orden del día es la defensa (y reproducción) de las ganancias de sus corporaciones multinacionales y capital financiero, por medio de la incautación internacional de los activos de intereses, tales como financieros, energéticos, comunicacionales y recursos naturales, además del dominio de mercados locales, más allá de facilitar la huida de capitales entre otros.

A tese central que procuramos explorar nesse artigo é de que o presente quadro político sul-americano tem exigido do imperialismo estadunidense uma redefinição estratégica, no sentido de neutralizar, debilitare, se possível for, destruir experiências/ tendências políticas regionais que não se alinham à sua política externa. Sob a máscara da defesa da democracia e do argumento de que as "políticas orientadas para o mercado" latino-americano correm risco, em razão de questões como delinqüência, crime organizado internacional, narcotráfico mundial e terrorismo global, a estratégia global do imperialismo estadunidense passa então a definir uma nova doutrina de guerra preventiva que justifica a utilização do poder bélico contra qualquer país, em nome de sua própria defesa. No cerne da questão o que -de fato- está em pauta é a defesa (e reprodução) dos interesses de suas corporações multinacionais e capital financeiro, por meio do confisco internacional de ativos lucrativos, tais como financeiros, energéticos, comunica-cionais e de recursos naturais, ademais do domínio de mercados locais.
The US foreign policy in the actual South American political board
Keywords: Militarization-Latin America; American Imperialism; Foreign Politics-United States; Militarización-Latinoamérica; Imperialismo estadounidense; Política externa-Estados Unidos; Militarização-América Latina; Imperialismo-estadunidense; Política externa-Estados Unidos